2006
DOI: 10.1038/nature05078
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent representation of visual categories in parietal cortex

Abstract: Categorization is a process by which the brain assigns meaning to sensory stimuli. Through experience, we learn to group stimuli into categories, such as 'chair', 'table' and 'vehicle', which are critical for rapidly and appropriately selecting behavioural responses. Although much is known about the neural representation of simple visual stimulus features (for example, orientation, direction and colour), relatively little is known about how the brain learns and encodes the meaning of stimuli. We trained monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
518
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(567 citation statements)
references
References 27 publications
45
518
3
1
Order By: Relevance
“…First, occipitotemporal, parietal, and motor regions were engaged early (first component) in processing. This is consistent with the role of occipitotemporal regions in the processing of visual forms (Ostwald et al, 2008), and parietal and motor regions in perceptual categorization (Freedman and Assad, 2006) and stimulus-response association processes (Toni et al, 2001). Second, processes related to perceptual judgments (i.e., associated with the second component) engaged prefrontal regions, consistent with the role of prefrontal cortex in categorization and adaptive cognitive processes (Miller, 2000;Duncan, 2001).…”
Section: Eeg-informed Fmri Mapping Of Regions Of Interestsupporting
confidence: 81%
See 1 more Smart Citation
“…First, occipitotemporal, parietal, and motor regions were engaged early (first component) in processing. This is consistent with the role of occipitotemporal regions in the processing of visual forms (Ostwald et al, 2008), and parietal and motor regions in perceptual categorization (Freedman and Assad, 2006) and stimulus-response association processes (Toni et al, 2001). Second, processes related to perceptual judgments (i.e., associated with the second component) engaged prefrontal regions, consistent with the role of prefrontal cortex in categorization and adaptive cognitive processes (Miller, 2000;Duncan, 2001).…”
Section: Eeg-informed Fmri Mapping Of Regions Of Interestsupporting
confidence: 81%
“…Recent studies suggest that learning alters later decision-related processes thought to reweight the contributions of early sensory representations (Dosher and Lu, 1999;Li et al, 2004;Law and Gold, 2008;Jacobs, 2009). Our findings suggest that learning modifies early recurrent processing (Roelfsema and van Ooyen, 2005;Roelfsema, 2006) within higher visual and parietal areas engaged in the integration (Ostwald et al, 2008) and categorization (Freedman and Assad, 2006) of global visual forms. Specifically, our findings showing that learning modulates shape processing in higher occipitotemporal regions (LO) sheds light on the contested role of temporal cortex in visual learning.…”
Section: Discussionmentioning
confidence: 73%
“…Such "number neurons" abstractly represent the number of items across space, time, and modalities (15,16,17). Number neurons have also been traced indirectly in the human brain using functional MRI (fMRI) (18,19).However, because neurons can be trained to represent behaviorally meaningful categories (20,21,22), it has been argued (23) that the presence of previously described number neurons in trained animals might be a product of intense learning, rather than a reflection of a spontaneous number sense. For the same reason, the coding scheme for numerosity has been debated (23): Is the spontaneous neuronal code for numerosity a summation code, as evidenced by monotonic discharges as a function of quantity (14,24), or a labeled-line code as witnessed by numerosity-selective neurons tuned to preferred numerosities analogous to those found in monkeys performing numerical tasks (25,26)?…”
mentioning
confidence: 99%
“…In agreement with the view that detections are discriminations of a stimulus from noise (11), elegant studies by Romo and coworkers (12, 13) reported neurons actively encoding the decision about the stimulus presence. The decision about stimulus absence, however, was represented as a default (baseline) neuronal response (12-16) for action-based detection decisions.When dissociated from action preparation or studied in a report-independent framework, decisions can be seen as distinct processes that are encoded as abstract categories (17)(18)(19). In a dotmotion discrimination task, neurons in the lateral intraparietal area were shown to encode the abstract decision about motion directions independently from how they signaled the associated motor response (20).…”
mentioning
confidence: 99%
“…When dissociated from action preparation or studied in a report-independent framework, decisions can be seen as distinct processes that are encoded as abstract categories (17)(18)(19). In a dotmotion discrimination task, neurons in the lateral intraparietal area were shown to encode the abstract decision about motion directions independently from how they signaled the associated motor response (20).…”
mentioning
confidence: 99%